Selective screening for inborn errors of metabolism using tandem mass spectrometry in West Kazakhstan children: study protocol - Zharmakhanova, Gulmira; Kononets, Victoria; Balmagambetova, Saule; Syrlybayeva, Lyazzat; Nurbaulina, Eleonora; Zhussupova, Zhanna; Sakhanova, Svetlana; Ayaganov, Dinmukhamed; Kim, Svetlana; Zhumalina, Akmaral (Frontiers in Genetics, 2024)
The lack of epidemiological data on the incidence of IEM is one of the reasons for the delay in the development of proper population-based newborn screening for IEM using the LC-MS/MS method in Kazakhstan. Currently, ENBS is being conducted in Kazakhstan for two hereditary diseases -phenylketonuria (PKU) and congenital hypothyroidism, the most represented screening diseases in most countries. This nationwide ENBS program based on biochemical tests started in 2007. Besides, in Kazakhstan, before the present study, state-funded MS/MS selective screening programs were implemented as sporadic pilot projects in some regions of the country without completion. Reports on these projects have not been published in peer-reviewed journals. As MS/MS neonatal screening is not mandatory in Kazakhstan, there are no uniform technical specifications for IEM screened by MS/MS in pilot studies. Hence, data on the frequency of IEM at the national level are not presented. For a country with no mandatory ENBS MS/MS program, selective screening can become essential for diagnosing IEM. The present research aims to develop and validate the LC-MS/MS method for simultaneously determining 51 metabolites in dry blood spots for IEM screening and clarifying age-related ranges for AAs, ACs, and SuAc in Kazakhstan children.